IMECCHI-DATANETWORK: empowering knowledge generation through international data network. (2017) - Pogam, Marie Annick Le; Metcalf, Amy; Johnsen, Søren Paaske; Hider, Phil; Patel, Alka; Kim, Hongsoo; Carlini, Emanuele; Perego, Raffaele; Quan, Hude; Gini, Rosa
No abstract available